Demonstration of Controlling the Spatiotemporal Dynamics of Optical Near-Field Excitation Transfer in Y-Junction Structure Consisting of Randomly Distributed Quantum Dots. (28th April 2014) - Nomura, Wataru; Naruse, Makoto; Aono, Masashi; Kim, Song-Ju; Kawazoe, Tadashi; Yatsui, Takashi; Ohtsu, Motoichi
Abstract : Solution searching devices that operate on the basis of controlling the spatiotemporal dynamics of excitation transfer via dressed photon interactions between quantum dots have been proposed. Long-range excitation transfer based on dressed photon interactions between randomly distributed quantum dots is considered to be effective in realizing such devices. Here, we successfully controlled the spatiotemporal dynamics of excitation transfer using a Y-junction structure consisting of randomly dispersed CdSe/ZnS core-shell quantum dots. This Y-junction structure has two "output ends" and one "tap end." By exciting one output end with control light, we observed increased excitation transfer to the other output end via a state-filling effect. Conversely, we observed reduced excitation transfer to the output ends by irradiating the tap end with control light, due to excitation of defect levels in the tap end. These results show the possibility of controlling the optical excitation transfer dynamics between multiple quantum dots.